Gross and Histomorphometric Changes in the Small Intestine of Anak and Marshal Broiler Hybrids - Levi, Usende I.; Lilian, Okafor C.; Njideka, Adaka; Thank God, Onyiche E.; C. Innocent, Nwaogu; N. Daniel, Ezeasor (Indian Journal of Veterinary Anatomy, 2013)
The growth pattern of Anak 2000 and Marshal broiler hybrids was compared using gross and light microscopic methods. Thirty chicks of both sexes of each hybrid were bought from 2 commercial hatcheries. They were reared until 10 weeks of age. Birds were humanely sacrificed at 2 weeks intervals beginning from the 2nd week till the 10th week of age . The live weights of each bird were obtained during different intervals. The mean live weight as well as the intestinal weight, length, and villi height increased with the age of the birds from 2nd-10th week. This was statistically significant (P < 0.05). There was no significant difference (P>0.05) between the mean body weights of the two broiler hybrids. In conclusion, both broiler breeds have similar growth pattern in terms of gross and histomorphometric features throughout the period of study.